Coronary artery diseases after right ventricular outflow tract reconstruction surgery. (25th November 2020) - Kwon, H; Bae, E.J; Kim, G.B; Lee, S.Y; Song, M.K; Lee, J.R; Kim, W.H; Kwak, J.G; Cho, S.K
Abstract: Background: The occurrence of coronary artery disease (CAD) is unknown to date in patients who have undergone the right ventricular outflow tract (RVOT) reconstruction surgery for congenital heart disease using a bioprosthetic valve or conduit. Purpose: We present the incidence and outcomes of CAD in patients who underwent RVOT reconstruction surgery in a single tertiary center. Method: From April 1986 to February 2019, 544 patients underwent Rastelli operation or pulmonary valve replacement for conotruncal anomalies at the Seoul National University Children's Hospital in Korea. The patient's medical records and imaging findings were analyzed retrospectively. Results: Significant coronary stenosis or occlusion were observed in 19 patients (3.5%) after RVOT reconstruction surgery. Their underlying diseases were pulmonary atresia in 8, tetralogy of Fallot in 3, double outlet right ventricle with pulmonary stenosis in 3, truncus arteriosus in 2, congenitally corrective transposition of great artery in 2, and congenital aortic stenosis in 1. Mechanism of CAD was compression of coronary artery by artificial conduit or valve in 10, intraoperative coronary injury in 7, and intramural course of coronary artery in 2 patients. The median number of RVOT reconstruction surgery before the diagnosis of CAD was 2 times (interquartile range: 2–3 times). The median age at diagnosis of CAD was 15 years (interquartile range: 9.5 - 25 years). The median time to detection of the CAD from the last RVOT reconstruction surgery was 9 years (interquartile range: 3.5–12.5 years). Involved coronary artery was right coronary artery (RCA) in 10, left anterior descending coronary artery (LAD) in 7, and left main coronary artery in 2 patients. Seven (36.8%) patients had underlying congenital coronary anomalies, such as single coronary artery, intramural course of the coronary artery, and anomalous origin of the coronary artery from an abnormal sinus. One patient died due to brain injury on extracorporeal membrane oxygenator after intraoperative coronary injury. Two patients with intramural course of coronary artery and one patient with high take-off of RCA which was compressed by adjacent calcified conduit underwent surgical repair of the CAD. One patient with recurrent ventricular tachycardia needed an implantable cardioverter-defibrillator. Nine patients are on medication for heart failure. Three patients with total occlusion of RCA or LAD showed well-developed collaterals from another normal coronary artery. Conclusion: CAD after RVOT reconstruction surgery are not common but can be fatal. Because the clinical significance of CAD and long-term prognosis are not known yet, we need to closely track the patient after RVOT reconstruction surgery. Indications for the management of the CAD should be prepared to prevent sudden cardiac death, arrhythmia, and ventricular dysfunction in these patients. Funding Acknowledgement: Type of funding source: None